The Effect of Physical Activity on Premenstrual Syndrome in Elementary School Teacher Education Students, Physical Education at The Indonesian Education University, Sumedang Regional Campus - Siti Adira Puspa Kania; Dinar Dinangsit; Dewi Susilawati (Universitas Negeri Semarang, 2025)
Menstruation is one of the signs of the development of the reproductive system in women. Menstruation states that women have reached the point of reproductive maturity ready to be fertilized, this is inseparable from Premenstrual syndrome which is a sign before menstruation. This study aims to determine the relationship between physical activity and symptoms of premenstrual syndrome. In this study using quantitative methods. Through 2 questionnaires of physical activity and premenstrual syndrome, the data obtained correlation between the dependent variable and the independent variable lies in the significance of the results of statistical calculations, namely the significance obtained is the Sig value. 0.195. Which has a number smaller than 0.05, therefore it is stated that there is no correlation between the two variables studied or the correlation in the two variables is not too significant or can be called weak. The conclusion is in line with the data obtained by the researcher, there is an influence of physical activity on premenstrual syndrome symptoms in women with data that 80% of students have a high level of physical activity and 68% of respondents stated that they had quite high premenstrual syndrome symptoms. This states that physical activity has an influence on premenstrual syndrome in female students, but the level of influence is not very significant in each individual.